Pengembangan bahan ajar ilmu pengetahuan Sosial melalui pendekatan saintifik berbasis lingkungan sekitar untuk peningkatan kemampuan berpikir ilmiah Siswa Sekolah Dasar - Devie Marliana (COLLASE (Creative of Learning Students Elementary Education), 2023)
This Study is a Research and Development (R&D). The development model used is the Four-D model adapted from Thiagarajan (1974) which consists of four stages including: defining, designing, developing, and disseminating. The development steps are: 1) analyze the needs of learning in primary school; 2) develop the design of initial products; 3) validation and revisions; 4) small group test; 5) large group test; and 6) disseminations. The experiment group are 45 students in SD Negeri 1,2,3 Jojo, the control group are 38 students in SD Negeri 1,3,4 Adiwarno and 13 students in SD Negeri 3 Jojo to obtain data. limited scale trial. Data was collected using observation guide, questionnaire of learning media validation, test, and documentation. Validation data analysed by accumulating the obtained scores of validation. Effectiveness data analysed by gain test, t test with 5% level of significance.